Efficacy and safety of EGFR-TKI combined with WBRT vs. WBRT alone in the treatment of brain metastases from NSCLC: a systematic review and meta-analysis - Li, Shuai; Xu, Shumei; Li, Luwei; Xue, Zhihong; He, Lang (Frontiers in Neurology, 2024)
Background The efficacy and safety of combining epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) with whole-brain radiotherapy (WBRT) for treating brain metastases in non-small cell lung cancer patients remains to be determined. Methods A systematic search was conducted using databases including PubMed, Embase, Web of Science, Cochrane, Wanfang, and China National Knowledge Infrastructure (CNKI), aiming to identify relevant clinical studies on the treatment of brain metastases originating from non-small cell lung cancer through the combination of EGFR-TKI and WBRT. Statistical analysis was performed utilizing Stata 17.0 software, covering clinical studies published until March 1, 2023. Results This analysis incorporated 23 randomized controlled trials (RCTs), involving a total of 2,025 patients. Of these, 1,011 were allocated to the group receiving both EGFR-TKI and WBRT, while 1,014 were assigned to the WBRT alone group. The findings reveal that the combination of EGFR-TKI and WBRT significantly improves the intracranial objective remission rate (RR = 1.57, 95% CI: 1.42–1.74, p < 0.001), increases the intracranial disease control rate (RR = 1.30, 95% CI: 1.23–1.37, p < 0.001), and enhances the 1-year survival rate (RR = 1.48, 95% CI: 1.26–1.73, p < 0.001). Additionally, this combined treatment was associated with a significant survival advantage (RR = 1.48, 95% CI: 1.26–1.73, p < 0.001) and a reduced incidence of adverse effects (RR = 0.65, 95% CI: 0.51–0.83, p < 0.001), particularly with respect to nausea and vomiting (RR = 0.54, 95% CI: 0.37–0.81, p = 0.002) and myelosuppression (RR = 0.59, 95% CI: 0.40–0.87, p = 0.008). However, no statistically significant differences were observed for diarrhea (RR = 1.15, 95% CI: 0.82–1.62, p = 0.418), and skin rash (RR = 1.35, 95% CI: 0.88–2.07, p = 0.164). Conclusion In contrast to WBRT alone, the combination of EGFR-TKI and WBRT significantly improves intracranial response, enhancing the objective response rate, disease control rate, and 1-year survival rate in NSCLC patients with brain metastases. Moreover, aside from mild cases of rash and diarrhea, there is no statistically significant increase in the incidence of additional adverse effects. Based on the comprehensive evidence collected, the use of third-generation EGFR-TKI combined with WBRT is recommended as the preferred treatment for NSCLC patients with brain metastases, offering superior management of metastatic brain lesions. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/#, CRD42023415566.